Selected Aspects of France’s Foreign Policy towards the United States during Emmanuel Macron’s Presidency from 2017 to 2022 - Pruchnicka, Paulina (Political Preferences, 2022)
The French diplomatic tradition has been going on for centuries and has influenced other parts of the world. One of France's most essential foreign policy directions is relations between France and the United States. It can be said to be friendship and hatred at the same time. The deep-rooted anti-Americanism in the French and the desire by Paris to return to great power status makes these relations even more difficult. In this article, I review France's foreign policy toward the United States from 2017 to 2022. In particular, I focus on analysing the aspect of superpower status, NATO membership and UN membership. I prove that these aspects have the greatest impact on Franco-American relations.